2020
DOI: 10.1039/c9ra10409g
|View full text |Cite
|
Sign up to set email alerts
|

Fast-response humidity sensor based on laser printing for respiration monitoring

Abstract: This work reports a facile and inexpensive laser printing fabrication of PEDOT:PSS micron line as a humidity sensor for respiration monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 32 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…Moreover, when the sensitivity of chemiresistors based on pristine PEDOT:PSS loses linearity around 70% RH [42] and reaches saturation around 80% RH, [43] the PEO/PEDOT:PSS-10 shows a rather linear growth with humidity even at high humidity over 80%, presenting a really good sensitivity of around 1.08 % /%RH. On the contrary, the PEO/PEDOT:PSS-40 response loses its linearity for humidity concentration superior to 80% RH, showing a sudden increase of its response, and therefore the sensitivity here could not be properly calculated.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, when the sensitivity of chemiresistors based on pristine PEDOT:PSS loses linearity around 70% RH [42] and reaches saturation around 80% RH, [43] the PEO/PEDOT:PSS-10 shows a rather linear growth with humidity even at high humidity over 80%, presenting a really good sensitivity of around 1.08 % /%RH. On the contrary, the PEO/PEDOT:PSS-40 response loses its linearity for humidity concentration superior to 80% RH, showing a sudden increase of its response, and therefore the sensitivity here could not be properly calculated.…”
Section: Resultsmentioning
confidence: 98%
“…[31,32] This polymer in its pristine form has been applied for humidity sensors dedicated to environmental control, [33][34][35][36][37] art protection, [38] indoor air quality monitoring, [39][40][41] and biomedical applications. [42] However, the evaluation of humidity sensing capacity observing whether there is an influence of VOCs found in breath has not yet been performed. Furthermore, a drop-casted film from this material was also fully tested and characterized toward humidity sensing as a chemiresistor and revealed a saturation limit after 80% relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…Impedance-type humidity sensors can be miniaturized by using conventional microfabrication processes and, thus, it is possible to apply the sensor to small animals. Although the tidal volume of respiratory air is smaller (1–2 mL [ 68 ]) and the respiratory rate is faster (80–200 bpm for rats) than those of humans, the sensor successfully monitored the respiratory signals from rats. The humidity sensor monitored the increase in respiratory rates of an anesthetized rat from anesthetization to recovery.…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…The humidity sensor monitored the increase in respiratory rates of an anesthetized rat from anesthetization to recovery. The change in rat respiration in response to drug injection was also monitored in real time by Wang et al [ 68 ].…”
Section: Types Of Fast-response Humidity Sensormentioning
confidence: 99%
“…The National Fire Protection Association claimed that 44% of firefighter death was because of abrupt cardiac deaths. 125 Kales and colleagues 126 reported that 45% of firefighter fatalities were cardiac related, so that many people die because of heart damage and not because of fire injuries. ECG is defined as a method to transmit heart electrical activity by placing electrodes on the body.…”
Section: Types Of Wearable Sensors and Their Weaknessesmentioning
confidence: 99%